The relationship between administrative academic staff's leadership styles and their level of emotional intelligence: a case study in UiTM Sarawak / Sueb Ibrahim - Ibrahim, Sueb (Research Management Institute (RMI), 2017)
As the context of leadership is changing, to lead effectively will be critical to the long term success of organizations. Therefore, academic leaders at higher education institutions need to combine several leadership qualities in order to succeed. Academic leaders have to develop their rational in establishing which leadership style will result to high performance outcomes and leadership effectiveness. Thus, the nature of the leader's emotional connectedness to others is apparently in the growing interest in numerous studies on the effect of emotional intelligence on leadership. Moreover, at present, there seems to be increasingly attention being given to organizational life and leadership and general agreement about the need to incorporate the role of emotion into research on academic leaders at higher education institutions. Research on effective leadership and emotional intelligence is growing. Yet, there still remains a gap on the relationships that exist between leadership and emotional intelligence especially at higher education institutions such as colleges and universities. Utilizing these connections, the main aim of this study was to identify the relationship of administrative academic staff’s leadership styles and their level of emotional intelligence. This study utilized the quantitative approach in gathering the data for this study. A total of 20 administrative academic staff of UiTM Sarawak participated in this study. Two adapted research instruments that were used for this study were Bass and Avolio's Multifactor Leadership Questionnaire (MLQ5X Form) that identified the administrative academic staff’s leadership styles, and Mayer - Salovey - Caruso Emotional Intelligence Test (MSCEIT) as used to operationalize emotional intelligence. The findings of this study were as follow. First, it indicated that the administrative academic staff perceived themselves as exhibiting a highly transformational leadership style as compared to the other two leadership styles, namely transactional and laissez- faire. Second, it revealed that the administrative academic staff assessed themselves as demonstrating more on